Facial expression recognition using AI - Shan, Jie (Инноватика-2025 : сборник материалов XXI Международной школы-конференции студентов, аспирантов и молодых ученых, 28-30 апреля 2025 г., г. Томск, Россия)
This paper explores the advancements and challenges in the field of expression recognition, an area of study that bridges psychology, computer science, and human-computer interaction. Expression recognition, particularly facial expression recognition, is pivotal in developing more intuitive and responsive human-computer interfaces, enhancing security systems, and improving social robotics and therapeutic applications. The research delves into the methodologies employed in capturing and analyzing facial expressions, ranging from traditional manual coding systems to cutting-edge artificial intelligence algorithms leveraging deep learning and computer vision techniques.